Financial Repression and Exchange Rate Management in Developing Countries : Theory and Empirical Evidence for India - Kohli, Renu (IMF Working Papers; Working Paper ;, 2001)
Most developing countries have imposed restrictions on domestic and international financial transactions at one time or another. Such restrictions have allowed governments to generate significant proportions of their revenues from financial repression while restraining inflation. The eventual fiscal importance of the revenues from seignorage and from implicit taxation of financial intermediation pose a challenge for financial reform and liberalization. This paper presents a model of the role of financial repression in fiscal policy and exchange rate management under capital controls. We show how a balance of payments crisis arises under an exchange rate peg without capital account convertibility in the model economy and how the instruments of financial repression may be used for exchange rate management. The model is compared to the experience of India, a country that exemplifies the fiscal importance of financial restrictions, in the last two decades. In particular, we discuss the dynamics leading up to devaluation in 1991 and the role of financial repression in exchange rate intervention afterwards.